Outcomes after injury prevention counselling in a paediatric office setting: a 25-year review - Mark R Zonfrillo; Michael A Gittelman; Kyran P Quinlan; Wendy J Pomerantz (BMJ Publishing Group, 2018)
Objective Injury is the leading cause of death and acquired disability in children. Primary care providers routinely provide age-appropriate injury prevention (IP) counselling during healthcare visits. The objective was to review evaluations of the effectiveness of office-based paediatric IP counselling research.Design This review identified studies from July 1991 to June 2016 of children <5 years and their caretakers to determine the effectiveness of office-based counselling on IP knowledge, behaviours and outcomes. Studies were included if they had: (1) an intervention for a family with a child <5 years of age; (2) an unintentional injury mechanism addressed during counselling; (3) one or more mechanisms recommended to be discussed for children <5 years in the 2007American Academy of Pediatrics Policy Statement; (4) counselling occurring in the office setting; (5) an assessment of an outcome (eg, change in knowledge, behaviour or injury occurrences); and (6) English-language publication. Study characteristics (whether the study was controlled, randomised and/or blinded), target safety behaviours, the sample size, outcomes assessed (injuries, behaviour changes and/or education changes) and demonstrated effects were summarised.Results Sixteen articles met inclusion criteria. Twelve articles were randomised controlled trials, three were non-randomised trials and one was a pretest and post-test study. Fourteen articles measured a change in knowledge or reported behaviour, four included observed behaviour change and five measured change in injury outcomes. Thirteen of the 16 studies had positive effects demonstrated for certain outcomes, including for fall, poisoning, burn, fire, traffic injury and drowning prevention, while 10 showed no differences between study groups for other outcomes.Conclusions Published outcomes-based IP-related counselling research in the primary care setting for young children is infrequent, and additional research is necessary to further describe the effectiveness of these primary prevention efforts.